Analisis Kualitas Data Bundel Infeksi Daerah Operasi (IDO) di Rumah Sakit - Rudy Kurniawan; Farid Agushybana; Sri Achadi Nugraheni (Politeknik Negeri Jember, 2022)
Data on the prevalence of Surgical Site Infection (SSI) at hospital in Semarang during February-April 2019 showed that there was a significant increase from 0,07% to 0,14%. One of the efforts to prevent infection of the operating area can be done with the application of IDO bundles. To analyze the data quality of the Operation Area Infection (IDO) bundle at Hospital. The research design used in this research is mixed methods. The population in this study is the IDO bundle document (secondary data) which is 149 data (data for December 2019) and officers related to the operation process (primary data). The 100 documents calculated using the Slovin how to get the data using a random technique. The sample for qualitative data in this research is health workers related to the operating process. Sources of triangulation are the head of the ward and infection control officers at the hospital. The sampling method in this study used non-probability purposive sampling. High quality category data IDO bundles that are shown with accuracy and precision, legitimate and valid as well as detailed and easy to find. This is supported by the number of available human resources, namely for one service unit, one IPCLN and according to placement. Other supports are competent and certified. The quality of the IDO bundle data at Hospital in Semarang is low. It is recommended that the hospital can develop a more comprehensive policy to improve the implementation of the effectiveness of using the IDO bundle data.